Building Self-Efficacy in Parenting Adult Children With Autistic Spectrum Disorder: An Initial Investigation of a Two-Pronged Approach in Role Competence - Leung, Cecilia Nga Wing; Tsang, Brenda; Huang, Doris Haiqi; Chan, Raymond Won Shing (Frontiers in Psychology, 2022)
Previous studies on parenting adult children with ASD were scarce, and their intervention protocols mainly were derived from established work with children. Development of an applicable adult-oriented protocol and demonstration of its effectiveness is warranted. The present study outlined the development and evaluation of Core Autism Parenting Skills (CAPS), a two-armed parenting self-efficacy (PSE) intervention for adult children with ASD. In CAPS, PSE is operationalized into four parent roles, each with requisite attributes, skills, and prescribed training. Twenty-seven parents with ASD children (aged 16 to 37) were recruited. They completed measures assessing their PSE, competence in the four parent roles, emotional well-being, and autistic symptoms of their children at pre-training, post-training and two-month follow-up. The intervention was well-received by the participants and reported significant improvements in PSE, parent role competence at post-training and two-month follow-up. The applicability of PSE and parent role competence in constructing effective parenting intervention for adult children with ASD was supported.